Analisis Hukum Perikatan dalam Konteks Digital : Tantangan dan Peluang di Era Industri 4.0 - Didit Firmansyah; Irsyal Ramadhan; Metha Jelita Kusuma; Regi Setraati (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
The increasingly developing internet-based technology has also influenced trade activities in society. With the internet, trading activities can be carried out electronically, or what is better known as electronic-commerce and abbreviated as e-commerce. Likewise in Indonesia. In carrying out e-commerce transaction activities, transaction activities from the time an offer is made by the seller (manufacturer) to the buyer (consumer) until the implementation agreement is issued, all buying and selling uses electronic data by utilizing the internet network both by means of computers and communication tools. such as gadgets and cell phones, so that buying and selling transactions can be carried out anywhere, anytime and in a very flexible way. With its unique characteristics, it sometimes creates problems of legal certainty. Wider problems occur in the civil sector because electronic transactions for e-commerce based buying and selling transactions have become part of national and international commerce.